Education for Elderly Spiritual Strengthening During the Covid-19 Pandemic - Dewi, Putu Adi Cahya (STIKES Advaita Medika Tabanan, 2023)
Elderly are the group of people who are most at high risk of infection corona virus. Age over 60 years and comorbid diseases such as diabetes, hypertension, chronic obstructive disease and cardiovascular disease are the main factors vulnerability of the elderly to COVID-19. Several studies have stated that spirituality be able to help the elderly to deal with the psychological impact of the pandemic, however, in practice, most of the elderly and their companions only focus on health problems in the biological/physical domain and ignore psychological, social, cultural and spiritual health. This activity aims to increasing spirituality of elderly during the COVID-19 pandemic at Tangguntiti Village, Selemadeg Timur District, Tabanan Regency, held on April 28, 2022. After education on spiritual strengthening of the elderly during the Covid-19 pandemic was carried out in Tangguntiti Village, Selemadeg Timur District, Tabanan Regency, the elderly were committed to improving their spiritual quality in daily life, in order to improve the psychological comfort of the elderly so that a good elderly body resistance is formed during the Covid-19 pandemic.